Functional SNP in 3′‐UTR MicroRNA‐Binding Site of ZNF350 Confers Risk for Age‐Related Cataract. Issue 11 (16th September 2016) - Gu, Shanshan; Rong, Han; Zhang, Guowei; Kang, Lihua; Yang, Mei; Guan, Huaijin
ABSTRACT: Many studies have suggested that individual susceptibility to age‐related cataract (ARC) may be associated with DNA sequence polymorphisms affecting gene regulation. As DNA repair is implicated in ARC pathogenesis and single‐nucleotide polymorphisms (SNPs) in the 3′‐terminal untranslated region (3′‐UTR) targeted by microRNAs (miRNAs) can alter the gene function, we hypothesize that the miRNA‐binding SNPs (miRSNPs) in DNA double‐strand break repair (DSBR) and nucleotide excision repair (NER) pathways might associate with ARC risk. We genotyped nine miRSNPs of eight genes in DSBR and NER pathways in Chinese population and found that ZNF350 ‐ rs2278414:G>A was significantly associated with ARC risk. Even though the Comet assay of cellular DNA damage indicated that all the subtypes of ARC patients had more DNA breaks in peripheral lymphocytes than the controls independent of rs2278414 genotypes, individuals carrying the variant A allele (AA and AG) had lower ZNF350 mRNA levels compared with individuals with GG genotype. Moreover, the in vitro experiment indicated that miR‐21‐3p and miR‐150‐5p specifically downregulated luciferase reporter expression in the cell lines transfected with rs2278414 A allele compared with rs2278414 G. These results suggested that the association of SNP rs2278414 with ARC might involve an altered miRNA regulation of ZNF350.